2014
DOI: 10.1590/1516-4446-2013-1120
|View full text |Cite
|
Sign up to set email alerts
|

Cortical morphology changes in women with borderline personality disorder: a multimodal approach

Abstract: Objective: Borderline personality disorder (BPD) is a devastating condition that causes intense disruption of patients' lives and relationships. Proper understanding of BPD neurobiology could help provide the basis for earlier and effective interventions. As neuroimaging studies of patients with BPD are still scarce, volumetric and geometric features of the cortical structure were assessed to ascertain whether structural cortical alterations are present in BPD patients. Methods: Twenty-five female outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
9
0
2
Order By: Relevance
“…As such areas are associated with affective regulation, such reductions might be biological substrates of BPD symptomatology. In a recent neuroimaging study using the same approach, we observed significant morphological abnormalities of cortical thickness, volume, mean curvature, metric distortion, area and depth of sulcus in such areas among BPD patients (Araujo et al, 2014). Such findings are in agreement with previous structural neuroimaging studies involving BPD patients, and highlight the involvement of these areas in the regulation of mood reactivity, impulsivity and social behavior, considered dysfunctional in these patients (Araujo et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…As such areas are associated with affective regulation, such reductions might be biological substrates of BPD symptomatology. In a recent neuroimaging study using the same approach, we observed significant morphological abnormalities of cortical thickness, volume, mean curvature, metric distortion, area and depth of sulcus in such areas among BPD patients (Araujo et al, 2014). Such findings are in agreement with previous structural neuroimaging studies involving BPD patients, and highlight the involvement of these areas in the regulation of mood reactivity, impulsivity and social behavior, considered dysfunctional in these patients (Araujo et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Lastly, the presence in our sample of both females and males overcome the limitation the two previous two studies including only females. As underlined by the authors [15] the inclusion of only female patients prevents to extend the results to all BPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the authors underlined in the discussion, their findings cannot be generalized since the sample included only females with BPD. Furthermore, Freesurfer analysis of cortical morphology, being automated, could have a series of limitations such as errors regarding processes of segmentation, normalization and skull extraction [15]. Another study on female BPD using Freesurfer package showed reduced cortical thickness in prefrontal cortex, left tempoparietal junction, bilateral temporal poles and bilateral paracentral lobules [7].…”
Section: Introductionmentioning
confidence: 99%
“…The relatively weak sensitivity of the approach is further complicated by the variability of indices used (volume vs. area); surface area data tend to show greater variability across individuals . Second, although surface‐based methods provide some benefits relative to voxel‐based methods, most of the surface‐based studies reported thus far did not account for hemisphere asymmetry or lateralization , although hemispheric asymmetries underlie, at least in part, the divergence in findings . Lastly, previous studies showed that BPD diagnosis and some symptoms declined with patient's age, cohort age differences thus may be contributing to the inconsistencies among reports .…”
Section: Introductionmentioning
confidence: 99%